The Childhood to Prison Pipeline: Early Childhood Trauma as Reported by a Prison Population. (July 2019) - Stensrud, Robert H.; Gilbride, Dennis D.; Bruinekool, Robert M.
This study explored the degree and type of childhood trauma experienced before the age of 18 years reported by prison inmates. The Adverse Childhood Experiences (ACE) instrument was administered to 328 incarcerated and/or recently released individuals. Participants included women, males convicted of sex offenses, and males convicted of low-risk crimes. The majority of respondents reported levels of childhood trauma substantially above that reported in the general population. Women and males convicted of sex offenses reported the highest degree of trauma. The discussion addresses how rehabilitation counselors can collaborate with others in the counseling profession for earlier identification of individuals who may be experiencing or have experienced childhood trauma and promote better trauma-informed transition services to postsecondary education and employment and reduce levels of incarceration.